2016
DOI: 10.1007/s00384-016-2524-7
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Helicobacter pylori infection rates in Lynch syndrome mutation carriers with and without a first-degree relative with gastric cancer

Abstract: The recommendation to screen for H. pylori is increasingly followed. The prevalence of infection in this patient group does not differ from the general population. Patients who had a first-degree family member with gastric cancer did not have a higher infection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
(20 reference statements)
1
20
0
Order By: Relevance
“…In our series, HP infection was observed in all intestinal-type GCs and the diagnosis of cancer was made by upper GI endoscopy in a work up for symptoms. HP infection has been reported in about 20% of GCs in LS [ 2 , 6 , 21 ]. No differences in the frequency of HP infection were observed between LS carriers and the general population [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our series, HP infection was observed in all intestinal-type GCs and the diagnosis of cancer was made by upper GI endoscopy in a work up for symptoms. HP infection has been reported in about 20% of GCs in LS [ 2 , 6 , 21 ]. No differences in the frequency of HP infection were observed between LS carriers and the general population [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This value resembles the results of a Dutch retrospective observational cohort study, considering the prevalence of H. pylori in LS patients. In their study, Soer et al (13) reported that 46% of LS patients from 5 Dutch hospitals had undergone screening for H. pylori (mainly by serology), and of those screened, 20% were found to be infected. However, this proportion was not higher in individuals with a family history of GC (13).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Soer et al (13) reported that 46% of LS patients from 5 Dutch hospitals had undergone screening for H. pylori (mainly by serology), and of those screened, 20% were found to be infected. However, this proportion was not higher in individuals with a family history of GC (13). In their study, Renkonen-Sinisalo et al (11) also found similar occurrence rates of H. pylori infection among mutation-positive and mutation-negative family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standardized incidence ratios for developing gastric cancer have been reported to be 2.9 and 6.1 for MLH1 and MSH2 mutations, respectively (24). The risk of Lynch syndromeassociated gastric cancer may be increased in countries with higher incidences of sporadic gastric cancer or high incidences of H pylori infection (60,61).…”
Section: Associated Urothelial (Upper Tract and Bladder) Cancersmentioning
confidence: 99%